The Role of probiotics in antibiotic-associated diarrhea, acute diarrhea and functional constipation in children - Korotko, Urszula; Biskupski, Mikołaj; Cygnarowicz, Aleksandra; Hosseinnejad, Negar; Mandziuk, Aneta; Sacher, Karolina; Turemka, Mariola; Witowska, Kinga; Wojtas, Aneta Klaudia; Zabojska, Krystyna; et al. (Journal of Education, Health and Sport, 2024)
Introduction and purpose Probiotics are widely used by parents of children, as well as by heathcare professionals. Because of their long history of presence on the market they have become an evident addition to the treatment of gastrointestinal disorders. The aim of this review is to emphasize what are the current recommendations for the use of probiotics in children in antibiotic-associated diarrhea (AAD), acute diarrhea and functional constipation, determine what the safety of their use is, and what to look for when choosing a product. Material and methods For this review, we used the literature available in PubMed and Google Scholar using the following keywords: “probiotics”, “probiotics in pediatrics”, “gut microbiota”, “acute gastroenteritis”, “AAD in children”, “functional constipation”. Brief description of the state of knowledge Probiotics are often used in pediatrics despite their uncertain efficiency. At the same time, there is a focus on the quality, purity and appropriate dosage of preparations available on the market. Extra precaution must be taken when administering a preparation or refraining from administering a probiotic to children with immune disorders. The benefit of their use mostly in AAD in children is difficult to determine. Conclusion Probiotics may be considered during antibiotic therapy in children if a broad-spectrum antibiotic is being used, the duration of therapy is prolonged, or there are other risk factors for AAD in children. In acute gastroenteritis, probiotics can be considered; however, their effectiveness is limited. Probiotics should not be used in the treatment of functional constipation. It is preferable to use probiotics in the form of a medicine. The efficacy of probiotics is both strain-specific and disease-specific.